Substantial Relations Making Global Reproductive Medicine in Postcolonial India - Bärnreuther, Sandra (Cornell University Press, 2021)
Substantial Relations examines global reproductive medicine in India, focusing on in vitro fertilization. Since the 1970s, India has played a central but shifting role in shaping global reproductive medicine-from a provider of raw material, to a producer of knowledge and technology, to a creator of a thriving medical market that attracts patients from all over the world. Relying on archival material and oral history, Substantial Relations traces the path of this transnational historical trajectory. This book also examines the contemporary making of IVF in Delhi. Drawing on ethnographic research in homes, hospitals, and laboratories, Sandra Bärnreuther provides deep insights into the intricacies of clinical life and everyday experience by depicting IVF users' quest for offspring and their fears of establishing unwanted ties, as well as the minute engagements of clinicians and laboratory staff with reproductive substances. Thinking through substances-metaphorically and materially-Sandra Bärnreuther provides a novel and rich analysis of the various relations that the burgeoning IVF sector in India has relied on and generated. Substantial Relations contributes to a broader understanding of reproductive medicine as a global phenomenon constantly in the making, situating India in the midst of, rather than peripheral to, this process.